AN ANALYSIS OF STUDENTS ABILITY IN READING COMPREHENSION DURING THE PANDEMIC OF COVID 19 AT X CLASS IN SMA NEGERI I BADAR ACADEMIC YEAR 2021/2022 - ABDUL RASIB; MUHAMMAD TAHIR; MERI VANCITO (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This study deals with the students’ ability in reading comprehension during tha pandemic of covid 19 at X class in SMA Negeri 1 Badar Academic Year 2021/2022. Its objective is to know student ability in reading comprehension during pandemic Covid 19. The research is done by collecting the data and scoring the result of the answer and quantitative method to find out the result. This research is enough to know the aim of this research is an analyzing of students’ in reading ability during the Pandemic of Covid 19 at X Class in SMA Negeri 1 Badar by focusing on Recount Text ability.The data was analyzed and researcher found The students who were taught The Pandemic Of Covid 19 got better achievement that those who were taught by using conventional technique that was Teacher. the highest score of the pre-test was 65 and the lowest was 45. While the highest score of post-test was 90 and the lowest was 70. The result of means of Pre-Test was 54.67 while the result of deviation standard was 6.18 And the result of means of Post-Test was 80.33. While the result of deviation standard was 5.91. From this research, it was found that the can cause a positive, which is proven from the result of the test, t_test>t_tableor ( 16.55> 2.04 ) there is significance Students Ability in Reading Chomprehension During Skill The Pandemic Of Covid 19